2018
DOI: 10.3126/jnhrc.v16i3.21419
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Modern Contraceptive Use among Adolescents in Nepal

Abstract: In Nepal, contraceptive use among married adolescents is low and has remained nearly stagnant since 2006, while little information is available about contraceptive use among unmarried adolescents. Nepal is committed to improve sexual and reproductive health rights among all the adolescents. Promoting modern contraceptive use especially among married adolescents is one of the key approaches in practice, to prevent HIV or sexual transmitted infections, avoid unintended pregnancy and sub-sequent unsafe abortion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 25 publications
4
12
0
Order By: Relevance
“…Adolescent girls aged 19 years were more likely to be using contraceptives at the time of the survey compared to 15-year-olds. This finding is consistent with those from other studies [8,29]. This could be attributed to older female adolescents being more mature and knowledgeable about contraception and the importance of contraceptive use, unlike younger female adolescents.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Adolescent girls aged 19 years were more likely to be using contraceptives at the time of the survey compared to 15-year-olds. This finding is consistent with those from other studies [8,29]. This could be attributed to older female adolescents being more mature and knowledgeable about contraception and the importance of contraceptive use, unlike younger female adolescents.…”
Section: Discussionsupporting
confidence: 92%
“…In recent surveys, adolescent girls who were separated, widowed, or divorced were also more likely to be using contraceptives compared to those who had never married. The findings are in line with those from other studies [10,29,30]. One study found that adolescent girls who were married or living with a man were significantly more likely to use contraception compared to those who were not married or living together with a partner [10].…”
Section: Discussionsupporting
confidence: 91%
“…This scenario was also reported in the studies conducted in Tanzania and Nepal where lack of quali ed staff affected the utilization of SRH services. 30,33,34,35 Achieving a meaningful reduction in adolescent sexual and reproductive health challenges faced by the country will require an urgent intervention in the area of training of health care providers which should be backed with a standard management guideline and procedure that should be available in all the health care facilities Although it is argued that the health system component is not the only aspect affecting the sexual and reproductive health of adolescents, the lack of such structure contributes to the poor sexual and reproductive health challenges of adolescents in Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…The low uptake of contraception services has been linked to many factors in developing countries including religious misperceptions and negative social norms around premarital sex and pregnancy [9,10]. Other factors include non-availability of modern contraception services [11][12][13], and poor knowledge and access to youth-friendly sexual reproductive health services from health workers and teachers [14]. Contraceptive use and continuation over sustained periods of time is an important issue for young people.…”
Section: Problem Statementmentioning
confidence: 99%